PENINGKATAN KEMAMPUAN ADAPTASI LANSIA DENGAN TERAPI KELOMPOK - muji adi; Nurul Mawaddah; Nurwidji Nurwidji (Jurnal Kesehatan dr. Soebandi, 2020)
Problems that often arise in the elderly are biological, health, psychological and social problems. These conditions can cause difficulties in the ability to adapt to other elderly people. When the elderly are unable to adapt it will cause stress, lose control over their lives, and lose their identity. The changes that occur require adaptation or adjustment to complete the task of development and achievement of self-integrity for the elderly. This service is done as an effort to improve the adaptability of the elderly by using group therapy. The provisions of the elderly who can be involved in group therapy activities are the elderly can participate in all sessions in group therapy and the elderly who do not experience activity limitations because group therapy will be carried out in groups, with the target audience in this activity are all the elderly in Sumbertebu Village, Bangsal District, Regency Mojokerto which is a number of 12 elderly. The method used was prior to group therapy by identifying the adaptive ability of the elderly using a questionnaire. This activity was carried out by visiting the elderly house and the implementation was divided into 2 groups, each group consisting of 6 people. Group therapy activities carried out as many as 4 sessions per group with a duration of 30-45 minutes each session. Assessment of the ability of elderly adaptation is done before and after group therapy by observation. Observations are made using verbal and non verbal communication including themes that can be expressed, communication habits, listening, problem solving processes in groups and body and facial expressions that describe the emotional state of members. The results of the evaluation that all elderly have increased the score of adaptation ability of the elderly both in physical, cognitive, emotional, social and spiritual aspects after participating in group therapy activities for 4 sessions. Furthermore, it is expected as a form of follow-up so that the activity of group therapy continues, it is necessary to empower group therapy as a routine activity carried out in Sumbertebu Village, Bangsal District, Mojokerto Regency.